2022
DOI: 10.3390/agriculture12040481
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Harvest Date on the Chemical Composition and Fodder Yield of Guizotia abyssinica (Guizotia abyssinica (L.f.) Cass.) under the Climatic Conditions of South-West Poland

Abstract: Guizotia abyssinica (Guizotia abyssinica (L.f.) Cass.) is regarded as a minor oilseed crop, which is important in terms of its nutritional value and potential uses. An important benefit of this crop is its cultivation for green matter and seed yield even under the difficult conditions of marginal cultivation. Guizotia abyssinica has not yet gained popularity in Europe. However, in a changing climate and taking into account its feeding value, it could gain in importance for ruminant nutrition in the near future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…In contrast to this observed evolution through the seasons, Ganchev et al [35] observed that leaves of P. shan tong collected in spring had a higher CP concentration than leaves collected in the late autumn. As compared with our results, the literature pointed out lower (17.4% [36]) and higher (22.6% [37] and (27.1%) [38]) CP contents in Paulownia These differences could be attributed partly to different climatic conditions, varieties studied, and harvesting time [32,35]. The CP of P. shan tong is considered moderate compared with leaves of Moringa oleifera, which reaches more than 27% CP [39], but similar to those recorded for alfalfa (17 to 19%) [40].…”
Section: Chemical Composition and Secondary Metabolitessupporting
confidence: 73%
See 3 more Smart Citations
“…In contrast to this observed evolution through the seasons, Ganchev et al [35] observed that leaves of P. shan tong collected in spring had a higher CP concentration than leaves collected in the late autumn. As compared with our results, the literature pointed out lower (17.4% [36]) and higher (22.6% [37] and (27.1%) [38]) CP contents in Paulownia These differences could be attributed partly to different climatic conditions, varieties studied, and harvesting time [32,35]. The CP of P. shan tong is considered moderate compared with leaves of Moringa oleifera, which reaches more than 27% CP [39], but similar to those recorded for alfalfa (17 to 19%) [40].…”
Section: Chemical Composition and Secondary Metabolitessupporting
confidence: 73%
“…This discrepancy could be attributed to variation in environmental conditions and the maturation state of the plant [33,34]. It is well documented that the concentration of CP in plants depends mainly on the harvest time, plant growth phase, fertilizer applied, and soil conditions [32,35]. However, the CP contents reported herein remained stable throughout the growing season and ranged in a very narrow interval, being 19.4% and 19.8% for the winter and spring harvests, respectively.…”
Section: Chemical Composition and Secondary Metabolitesmentioning
confidence: 58%
See 2 more Smart Citations
“…19 The protein content of sugar beet leaf on a dry matter basis was found to be 10% 19 and 24.02%. 15 These differences in the chemical composition of the leaves may vary depending on many factors such as 20 The high protein content and the availability and abundance of raw materials allow sugar beet leaves as an alternative source for protein concentrate production. 15 Determination of protein isolation methods and parameters Determination of the pH value of extraction Extraction was carried out at pH values of 7, 8, and 9 according to the extraction procedure of the isoelectric precipitation method.…”
Section: Chemical Composition Of Sugar Beet Leavesmentioning
confidence: 99%